A new mathematical model to improve encryption process based on Split-Radix Fast Fourier Transform algorithm - Abdulle Hassan Mohamud (Frontiers in Computer Science)
This paper introduces a new encryption method aimed at improving the cryptography process through the use of splitting radix Fourier Transform technique called Split-Radix Fast Fourier Transforms (SRFFT). The proposed method is based on splitting the FFT radix-2 and radix-4 algorithms to achieve improved information assurance by SRFFT two phases. The first phase applies direct computation of SRFFT algorithm on input plaintext to produce a ciphertext and the second phase applies the reversing SRFFT algorithm to decipher. Several types of cryptoanalysis attacks such as brute-forcing, autocorrelation and dictionary attacks are comparatively evaluated and the end result of SRFFT evaluation indicates that SRFFT is preferable in many practical encryption applications since SRFFT complexity increases with the range of split-radix computations thus eliminating the potential chances of cryptanalysis attacks.